Perceptions of preschoolers and parents on forest pollution - Demirkaya, Hilmi; Köç, Ahmet; Sunay, Serap; Duygu, Hüseyin; Mol, Aslı; Günaydın, Gülsevil; Günaydın, Muhammedi Abdulkerim (Frontiers in Forests and Global Change, 2024)
An examination of preschool children’s perceptions and attitudes towards the environment and forests has recently been conducted. However, little research has been conducted on preschool children’s and their parents’ perceptions of clean and dirty forests. It is essential to investigate these perceptions to increase children’s interest in and sensitivity to the environment, thereby fostering their growth as responsible individuals protecting the natural world. This study aimed to address this knowledge gap by examining the perceptions of clean and dirty forests held by 40 5-6 year old students and 40 parents, randomly selected from two pre-schools, one attended by children from high socioeconomic families and the other by children from low socioeconomic families, in a Mediterranean coastal city in southwestern Turkey. A semi-structured questionnaire was used to collect sociodemographic information and perceptions of clean and dirty forests. Drawing sheets were also distributed to the students to draw pictures of clean and dirty forests. The results showed that individuals with higher educational levels had more complex and conscious perceptions of clean forests. Children considered abstract concepts, such as supernatural forces and fossil fuels, whereas parents focused on the level of awareness and conservation status. Parents and children with lower levels of education focus on more concrete and everyday factors such as litter and natural disasters. Individuals with higher socioeconomic status generally associated forest cleanliness with conscious behaviours and conservation, whereas those with lower socioeconomic status associated it more with polluting factors. This investigation provides valuable insights into the management and control of local forests by incorporating the perspectives of children and their parents for promoting responsible and sustainable tourism practices.